Long‐term recovery and food web response of benthic macrofauna following cessation of bottom trawling in a marine protected area - Mattias Sköld; Mats Blomqvist; Clare Bradshaw; Patrik Börjesson; Peter Göransson; Håkan Wennhage (Conservation Science and Practice)
Abstract The understanding of the depletion of species and communities and recovery following the reduction of pressures is fundamental in conservation biology. The impact of bottom trawl fisheries on benthic communities has been well studied, but there are few studies of the long‐term recovery after the cessation of bottom trawling. Here we followed the recovery of the benthic macrofaunal community over 12 years in a large (426 km2) no‐take zone (NTZ) area in the south Kattegat after demersal trawling was stopped and compared it to a nearby area where trawling continued. Using multivariate analyses, we found shifts in the community composition. Two species of burrowing brittle stars, Amphiura filiformis and Amphiura chiajei, dominated abundance and biomass and decreased in the closed area (abundance effect size A. filiformis 48%; A. chiajei 45%). In parallel, there was an increase in benthivore flatfish. Stomach contents of the dominating flatfishes matched the availability of benthic prey taxa, and brittle stars were the staple food. Food web effects thus appear to override the decrease in mortality of the dominant macrofauna caused by the cessation of trawling in the NTZ. The recovery response in the species community in the NTZ correlated with the pattern in community composition along a chronic bottom trawling intensity gradient in the same area. This indicates that the recovery of the benthic community is not random but follows a successional pattern that can also be observed in chronic states of disturbance from bottom trawling. This is important information from the perspective of management efforts to restore marine ecosystems from the impact of bottom trawl fisheries, as it indicates that reduced effort may lead to predictable recovery.